Domestic Pig (Sus scrofa) as an Animal Model for Experimental Trypanosoma cruzi Infection - Yauri, Verónica (Am J Trop Med Hyg, 2016)
Pigs were infected with a Bolivian strain of Trypanosoma cruzi (genotype I) and evaluated up to 150 days postinoculation (dpi) to determine the use of pigs as an animal model of Chagas disease. Parasitemia was observed in the infected pigs during the acute phase (15–40 dpi). Anti-T.cruzi immunoglobulin M was detected during 15–75 dpi; high levels of anti-T.cruzi immunoglobulin G were detected in all infected pigs from 75 to 150 dpi. Parasitic DNA was observed by western blot (58%, 28/48) and polymerase chain reaction (27%, 13/48) in urine samples, and in the brain (75%, 3/4), spleen (50%, 2/4), and duodenum (25%, 1/4), but no parasitic DNA was found in the heart, colon, and kidney. Parasites were not observed microscopically in tissues samples, but mild inflammation, vasculitis, and congestion was observed in heart, brain, kidney, and spleen. This pig model was useful for the standardization of the urine test because of the higher volume that can be obtained as compared with other small animal models. However, further experiments are required to observe pathological changes characteristic of Chagas disease in humans.